STRATEGI KOMUNIKASI CONTENT MARKETING SHANI AMELIA DALAM MEMBANGUN BRAND ENGAGEMENT PRODUK @YUIREOFFICIAL DI INSTAGRAM - Gogali, Venessa Agusta; Utomo, Ichsan Widi; Erlangga, Christoper Yudha (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This study aims to analyze the content marketing communication strategy implemented by Shani Amelia to build brand engagement for @yuireofficial products on Instagram. The research employs a descriptive qualitative method, using content analysis based on the AIDA model (Attention, Interest, Desire, Action) and measures brand engagement through three dimensions: Cognitive, Emotional, and Behavioral. The study finds that Shani Amelia's communication strategy effectively captures the audience's attention through Instagram Stories featuring aesthetic visuals and relevant promotional narratives. It fosters interest and desire through personal reviews and active interactions in the comment section. Additionally, brand engagement for @yuireofficial is established through the audience's trust in Shani Amelia's authenticity as an influencer, alongside active participation in promotions and purchases. The findings indicate that strategically applying the AIDA model, combined with managing the three dimensions of brand engagement, can significantly enhance consumer loyalty and involvement with the brand